ANALISIS CRYPTOCURRENCY MENGGUNAKAN SISTEM PAKAR BERBASIS FORWARD CHAINING DAN CERTAINTY FACTOR - Fattahuddin, Muhammad Rizky (Jurnal Teknologi Informasi, 2025)
Cryptocurrency has become a crucial subject in the global financial ecosystem. This paper addresses the analysis of cryptocurrency using an expert system approach based on forward chaining and certainty factor. The objective is to develop a framework capable of predicting crypto market behavior with high accuracy. The method utilizes an expert system to analyze historical data, identify patterns, and consider factors influencing the value of crypto assets. Forward chaining enables the system to incrementally build knowledge, while certainty factor accounts for the confidence level in assessments. Through careful experimentation and evaluation, the results indicate a promising level of accuracy in predicting cryptocurrency market movements. This research provides a foundation for further development in cryptocurrency market analysis and the application of expert systems in the context of modern finance.